Riesgos derivados de las actividades laborales en los trabajadores del Vivero Municipal del GAD Chone - Mendieta Vélez, Jean Carlo (2022)
The objective of the investigation was to evaluate the risks present in the work activities of the workers of the Municipal Nursery of the GAD Chone, for the elaboration of an occupational safety protocol. For this, it was divided into three phases: the first was to identify work activities by collecting information through inspection, interviews and surveys, where the result was that the institution carried out 6 processes with their respective activity, and a total of 20 tasks that expose workers to different occupational risks. After this, the dangers were identified through the GTC45 Matrix, obtaining as a result the existence of biological risks (27), security conditions (17), chemical (14), biomechanical (14), physical (8) and natural phenomena. (5), in all areas of the Municipal Nursery. The second phase consisted of weighing these risks with the help of the Colombian Technical Guide where each hazard was evaluated by existing risk in the different processes of the study area, which resulted in the risks with the highest levels denominated as "No Acceptable” come from exposure to biomechanical, safety and chemical hazards. Additionally, risks were found with a medium and low level designated as "Improveable” and “Acceptable" that were of a biological, physical and psychosocial nature. The third and final phase consisted of developing an occupational safety protocol to minimize the risks present in workers, based on the results obtained in the identification and assessment of risks.